The pollen yield of selected colonies of Apis mellifera as influenced by physical factors and vegetation flowering patterns - Remo, Marie Celeste N. (2001)
This study aims to determine the patterns of pollen yield of selected colonies of Apis mellifera as influenced by physical factors and flowering vegetation patterns surrounding the apiary site. Pollen yield was consistently low in a synchronized manner in the three populations from the first up to the seventh week and was exceptionally high at the 9th and 10th week. Brood rearing may be responsible for the exceptionally high pollen yield in those weeks since it was previously reported to occur in these months. Floral vegetation was most abundant at 9th, 10th, 8th and 3rd weeks of sampling periods which is also synchronized with extremely high pollen yields. These results indicate that pollen yield maybe influenced by floral vegetation surrounding the apiary. Using the Spearman Rho Correlation Analysis at a significance level of a=0.05; wind velocity, sunshine duration, temperature, relative humidity, and rainfall are not significant or correlated to pollen yield and a moderate negative correlation between rainfall and pollen yield. As temperature increases there is medium corresponding increase in the pollen yield. As rainfall increases there is a corresponding moderate decrease in the pollen yield. There is a highly significant positive correlation of floral vegetation on pollen yield with a correlation significant of 0.840. this result implies that floral vegetation exerts a highly significant influence on the observed pollen yield
Thesis (BS Biology) -- University of the Philippines Mindanao, 2001